2018
DOI: 10.3390/informatics5020026
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Networks for Human Activity Recognition Using Body-Worn Sensors

Abstract: Human activity recognition (HAR) is a classification task for recognizing human movements. Methods of HAR are of great interest as they have become tools for measuring occurrences and durations of human actions, which are the basis of smart assistive technologies and manual processes analysis. Recently, deep neural networks have been deployed for HAR in the context of activities of daily living using multichannel time-series. These time-series are acquired from body-worn devices, which are composed of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 153 publications
(85 citation statements)
references
References 27 publications
0
85
0
Order By: Relevance
“…This underlines the increasing significance and research interest in HAR for P+L. The application covers a wide range of sectors, such as manufacturing and assembling [58,86], warehousing [72,83,85], construction [90] and maintenance [11,14]. Warehousing, in particular order picking, is the only sector in logistics.…”
Section: Domainmentioning
confidence: 99%
See 4 more Smart Citations
“…This underlines the increasing significance and research interest in HAR for P+L. The application covers a wide range of sectors, such as manufacturing and assembling [58,86], warehousing [72,83,85], construction [90] and maintenance [11,14]. Warehousing, in particular order picking, is the only sector in logistics.…”
Section: Domainmentioning
confidence: 99%
“…However, the other datasets utilised in these contributions do involve locomotion activities. The remaining publications [72,76,83] from P+L apply HAR methods on both stationary working processes and locomotion activities. Apart from Reining et al [85], the observed contributions in the domain of P+L assume that the activity definition is known at design time and is not going to change at run time of a HAR method (see Section 1).…”
Section: Activitymentioning
confidence: 99%
See 3 more Smart Citations